Analysis of Consumer Behavior in The Decision-Making Process of Vegetable Purchase During the Covid-19 Pandemic at Bu Dipo’s Vegetable Store - Reo Sambodo (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2022)
Research to explain the characteristics of vegetable consumers at Bu Dipo’s store, analyze the decision-making process of buying vegetables, and explore the behaviour of vegetable consumers at Bu Dipo’s store. Data analysis used descriptive analysis, Fishbein multi-attribute, and Rank Spearman correlation. The attributes studied include; price, taste, nutritional content, colour, aroma, freshness, packaging, neatness, durability, shape and size, brand, product quality, and expiration information. Vegetables have the advantage of freshness attributes, nutritional content, and expiration information from other features after consuming them. The characteristics of consumers who buy vegetables at BU Dipo’s store are primarily women aged 31-40 years old, working as private employees with an income of IDR3.000.000 - IDR4.000.000 per month, and having two family members to support. In making vegetable purchasing decisions, the freshness factor is an attribute that influences consumers in buying vegetables at Bu Dipo’s store. Characteristics of consumers, namely age, income level, education level, and the number of family members covered, have no significant relationship with consumer behaviour towards purchasing vegetables at Bu Dipo’s store. Researchers can give suggestions to improve the quality of vegetable freshness and open branches to reach more consumers.